CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (CSRD) DALAM MENUNJANG KINERJA UMKM ART SHOP DI KAWASAN NUSA DUA BALI - I Gusti Ayu Ratih Permata Dewi (Universitas Mercu Buana, 2019)
This study aims to analyze the implementation of Corporate Social Responsibility Disclosure (CSRD) in supporting UMKM Performance in the Nusa Dua Region of Bali. CSR is not only done by large companies, but has been done in Small and Medium Enterprises. This research applies descriptive qualitative data analysis method. The total UMKM artshop in the Nusa Dua area is 75 UMKM. To answer the research problem, the data analysis method used is calculating the corporate social responsibility index (CSRI), calculating profit margins at the MSME artshop, analyzing and describing the reorder from customers and marketing expansion, CSRI crosstab analysis with profit margins, further describing and analyzing the implementation corporate social responsibility (CSR) on the performance of UMKM. Based on the results of the study found that the level of implementation that has been carried out by the owner or manager of UMKM artshop who became respondents in this study included in the high category. The CSR implementation that has been carried out by UMKM artshops in the Nusa Dua area mostly does not support the financial performance of UMKM but supports its non-financial performance.